An approximation of a common fixed point of nonexpansive mappings on convex metric spaces - W. Anakkamatee (2018)
Sokhuma and Kaewkhao (2011) introduced an iteration scheme to compute a common fixed point of a single-valued nonexpansive mapping and a multivalued nonexpansive mapping on a uniformly convex Banach space. In this paper, we extend the above result of Sokhuma and Kaewkhao from a single-valued mapping to a countable number of mappings and, at the same time, we extend the underlying spaces to strictly convex Banach spaces. The corresponding results are also obtained for the CAT(0) space setting. © 2012 Anakkamatee and Dhompongsa; licensee Springer.